WORD REPRESENTATION OF THE EMOTION OF ANXIETY IN ELDERLY WOMEN: PSYCHOLINGUSITIC-PRAGMATIC CASE STUDIES - Wini Tarmini; Nani Solihati; Ina Nurannisa (RETORIKA: Jurnal Bahasa, Sastra, dan Pengajarannya, 2023)
Anxiety problems often occur in elderly women. This study aims to describe the word representation of anxiety emotion in elderly women. This research uses qualitative approach. The analysis of the data collected using the techniques of recording, listening, note-taking, and skillful involvement. The results show that elderly women have a fairly high level of anxiety. When the psychological disturbance occurs, feelings such as worry, anger, boredom, disappointment, sadness, and confusion appear with lingual markers such as must, why, do not understand, strange, disappointed, sorry, and confused. When no psychological disturbances arise, feelings of gratitude and disappointment with lingual markers such as grateful, pray for me, alhamdulillah, unfortunately. Factors that cause the emergence of anxious emotions are circumstances that do not match expectations and desires and are having difficulty accepting reality.